Efektifitas Penggunaan Metode Tutor Sebaya Pada Kegiatan Pembelajaran Ekstrakurikuler Paduan Suara Di SMA Negeri 2 OKU - Mukti Safi’i; Nofroza Yelli; Feri Firmansyah (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This researcher aims to find out whether there is effectiveness in implementing the peer tutoring method on choir learning outcomes in class X at SMA Negeri 2 OKU. The research method used in this research is Pre Experimental Design, namely the One-Group Pretest-Posttest Design form. In this research, researchers used the Random Sampling technique, namely a random sampling technique. So the sample in this study was the choir extracurricular class, totaling 18 male students and 12 female students. The data collection technique uses tests in the form of practical tests and data analysis uses the t-test. The results obtained an average post-test score of 82 and pre-test score of 69.5. The scores obtained by the post-test scores are better than the pre-test scores. This is because treatment using the peer tutoring method is indeed effective in learning outcomes for choirs by singing the song Indonesia Raya. Then, based on normality testing, normal distribution data is obtained, then analyze the final test data as described previously. It is known that the t test hypothesis tcount ˃ ttable with tcount˃ = 10.68 and ttable = 1.69. So H0 is rejected and Ha is accepted or tcount ˃ ttable = 10.68 ˃ 1.69. Thus, it can be concluded that there is the effectiveness of the peer tutoring method on choir learning outcomes for extracurricular students at SMA N 2 OKU.